Landed Traders, Trading Agriculturalists? Land in the Economy of the Italian Diaspora in the Greek East*. (24th July 2017) - Eberle, Lisa Pilar; Le Quéré, Enora
ABSTRACT: This paper revises current understandings of the rôle of land in the economy of the Italian diaspora in the Greek East in the second and first centuriesb.c ., arguing that these Italians owned more land than has previously been assumed and that many of these Italian landowners practised a highly commercialized form of agriculture that focused on high-end products. This strategy shaped what empire meant both locally and in Italy and Rome, where the products they marketed fed into the ongoing consumer revolutions of the time. After discussing the evidence for the extent of Italian landholdings and examining their exploitation in three case studies, we conclude by reflecting on the long-term history of such landholdings in the provinces and the implications for our understanding of Roman imperialism more generally.